USE OF BIOTECHNOLOGY IN THE HYDROPARK RESERVOIR IN RIVNE - Likho, Olena; Voznіuk Nataliya; Turchyna, Kateryna; Brezhytska, Olena (Вісник Національного університету водного господарства та природокористування. Серія «Сільськогосподарські науки», 2020)
The article substantiates the expediency of using biotechnologies in order to improve the quality of water in the hydropark and the Ustya river within the limits of Rivne. Conditions of surface runoff formation were investigated and the main factors determining the water quality in the reservoir were determined. The results of water quality assessment in the hydropark were presented. It was revealed that the biggest contribution to the formation of water quality in the reservoir, as well as in the Ustya river, are heavy metals: iron, manganese, copper, zinc, and phosphates. The use of bioplateau as one of the types of biotechnology was proposed and a set of measures for improving the quality of water in the hydropark and Ustya river were presented.